Tomosynthesis Confirms the Findings of Ultrasonography and Magnetic Resonance Imaging of the Breasts - Asma'a A. Al Dabbagh,; Sarah K. Hagi, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Two-dimensional mammography has low sensitivity and often needs to be combined with other investigations. Tomosynthesis, a three-dimensional breast imaging technique, can be superior to mammography, in terms of size measurements and differentiation of breast lesions. We describe the case of a 41-year-old woman with a breast lesion imaged using mammography, ultrasonography, magnetic resonance imaging and tomosynthesis. Mammography showed heterogeneously dense parenchyma with a cluster of pleomorphic microcalcifications. Ultrasonography showed a poorly defined breast lesion and two enlarged left axillary lymph nodes. Magnetic resonance imaging revealed an irregular, persistently enhancing lesion and three abnormal left axillary lymph nodes. Biopsy confirmed the diagnosis of carcinoma. Tomosynthesis confirmed the breast lesion as well as the three abnormal lymph nodes. Thus, tomosynthesis plus mammography provided as much diagnostic information as the other tests combined and may be useful for the screening and diagnosis of breast cancer.